2017
DOI: 10.1177/0194599817697048
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided Design and 3‐Dimensional Printing for Costal Cartilage Simulation of Airway Graft Carving

Abstract: Autologous cartilage grafting during open airway reconstruction is a complex skill instrumental to the success of the operation. Most trainees lack the adequate opportunity to develop proficiency in this skill. We hypothesized three-dimensional (3D) printing and computer-aided design can be used to create a high-fidelity simulator for developing skills carving costal cartilage grafts for airway reconstruction. The rapid manufacturing and low cost of the simulator allow deployment in locations lacking expert in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…(***p < 0.001; ****p < 0.0001). (28). The scores in our study were comparable to those observed in the original study of this material (with a higher n of 12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(***p < 0.001; ****p < 0.0001). (28). The scores in our study were comparable to those observed in the original study of this material (with a higher n of 12).…”
Section: Discussionsupporting
confidence: 89%
“…The material was assessed by 2 experienced, blinded surgeons who rated the material 4 out of 5 overall on a Likert scale, and between 3 and 4 for properties such as texture, firmness, bending and carving ( 7 ). This material combination has since also been validated in producing simulated costal cartilage for airway reconstruction ( 28 ). The scores in our study were comparable to those observed in the original study of this material (with a higher n of 12).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, in the case of AER the great potential of using these technologies lies in the possibility of obtaining very precise and specific geometries of the patient’s costal cartilage. This results in the production of simulators that can no longer be used just for training with a “general” geometry, but also for a realistic preoperative simulation with a “custom” geometry [61,62]. Figure 4 shows the steps necessary for the production of the replica of the costal cartilage.…”
Section: Methods To Simulate Ear Reconstructionmentioning
confidence: 99%
“…This method can be used for aims of medicine, veterinary medicine, zootechny and related areas where MRI or histological reconstructions do not provide a full-fledged three-dimensional view [3,4,10].…”
Section: Examples Of Images Reconstruction In Arbitrary Sectionsmentioning
confidence: 99%
“…Another disadvantage of the method associates with utilization of digital raster photographs. 3D modeling can improve the efficiency of various solving aims tasks, including endoprosthetics [5,8,10,15,26,27].…”
Section: Introductionmentioning
confidence: 99%